Statistical Assessment of the Ecological Situation: The Case of the Republic of Azerbaijan - T. H. Tamrazov (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
The economic development in a country depends on the continuous development of its regions. This issue can be effectively addressed by statistical assessment of the real situation in economic regions of a country by use of key sustainable development indicators. Development factors at regional level (ecological, economic, and social) are not studied as a complex, which raises the need for and importance of comprehensive statistical analyses of the data on environmental performance at region and country level. The article contains a statistical analysis of these indicators for the Republic of Azerbaijan. The period from early 2000s till 2017 is covered. The analysis is made on the official statistics of the Republic of Azerbaijan. The indicators under study include: distribution of land by purpose, specially protected areas, state nature reserves, air temperature, air temperature in Baku city, average annual precipitation, average annual precipitation in Baku city, amount of pollutants emitted in the air, domestic wastes generation etc. The analysis also demonstrates the need to improve the quality of the primary statistical data. Conclusions and recommendations provided in the article are formulated from the results of the statistical analysis.